Предмет: Математика,
автор: Snowflake2000
Х во второй степени(Х+1)-(Х+2)(2Х-3)=Х во второй степени(Х-1)
Ответы
Автор ответа:
0
Х^2 *(Х+1)-(Х+2)(2Х-3)=Х^2 *(Х-1)
Х^3+x^2-2х^2+3x-4x+6=Х^3-x^2
Х^3+x^2-2х^2+3x-4x+6-Х^3+x^2=0
3x-4x+6=0
-x=-6
x=6
Х^3+x^2-2х^2+3x-4x+6=Х^3-x^2
Х^3+x^2-2х^2+3x-4x+6-Х^3+x^2=0
3x-4x+6=0
-x=-6
x=6
Автор ответа:
0
реши пожалуйста еще это http://znanija.com/task/5649052
Похожие вопросы
Предмет: Алгебра,
автор: mokintim
Предмет: Русский язык,
автор: dianagutulenko
Предмет: Алгебра,
автор: Аноним
Предмет: Геометрия,
автор: Аноним
Предмет: Математика,
автор: chelovekizdoti